Health Status of Nurses of Hospitals Dependent to Shahroud Medical University - Ali Darvishpoor Kakhki; Hossen Ebrahim; Hamid Alavi Majd (Iran University of Medical Sciences, 2009)
Background and Aim: Health is a right for humans. The most health service givers at health organization are nurses. Hence, they have important role at improve health status of community. But, they are exposed with different stressors that decrease health status. Hence, this study has been conducted to examine health status and evaluate correlation between health status and occupaitonal and demographic variables of them. Materials and Methods: This study is a descriptive research that conducted on nurses of hospitals dependent to shahroud medical university. Demographic and occupaitonal characteristics questionnaire and also short form health survey (SF-36) were used to data collection. Nurses respond by s elf-administered method to questionnaires. Data were analyzed by descriptive and inferential statistic with SPSS software, windows version.   Results: 158 nurses participated in this study. Upon to result, 75.8% of subjects were female, 24.2% male and average age were 32.48±8.31 year. The range of mean of health status scores in different domains was variants from 38.20±25.26 for bodily pain to 71.94±24.38 for physical functioning. There were significant relations between health status different dimensions and variables of age, recuritment status, work shift, clinial ward and years in profession. The statistical tests didn't reveal significant relations between sex, marital status and educational level with health status different dimensions.   Conclusion: The findings of this study showed that nurses suffer critically of bodily pains problem in comparison with other health status dimensions . Therefore attntion to health status of nurses especially bodily pains problem and its relations with demographic and occupaitonal variables to improvement health status of nurses is necessary.